If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -20r + 16y = 6r Reorder the terms: -20r + 4y + 16y = 6r Combine like terms: 4y + 16y = 20y -20r + 20y = 6r Solving -20r + 20y = 6r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-6r' to each side of the equation. -20r + -6r + 20y = 6r + -6r Combine like terms: -20r + -6r = -26r -26r + 20y = 6r + -6r Combine like terms: 6r + -6r = 0 -26r + 20y = 0 Add '-20y' to each side of the equation. -26r + 20y + -20y = 0 + -20y Combine like terms: 20y + -20y = 0 -26r + 0 = 0 + -20y -26r = 0 + -20y Remove the zero: -26r = -20y Divide each side by '-26'. r = 0.7692307692y Simplifying r = 0.7692307692y
| [x+7]=[x-5] | | (11-z)z= | | 24x^2-17x=0 | | x^2-2x+15=0 | | (6a^3b^3+3a^4b^2)-(3a^4b^2-6a^3b^3)= | | x^2=2x-2 | | 176=-16n | | 34x=14 | | -60=20x | | .01x=6 | | 3a^2+4a=2a^2-2a-9 | | 0=n+16 | | 2x-1=5x | | Y-10y+16=0 | | 7(3p+3)-7p= | | 6*3= | | 5j-9(5g+7u)+2-32= | | 6.3= | | 6x^3-7x^2+7x+9=0 | | 8x+7(-4+3x)= | | 3+2(1-5m)= | | 4(3n+1)-5= | | -3k+6(3k+3)= | | 3x^2-17x=6 | | 64k^2-81=0 | | 24n^2+16n=0 | | 4x^2-24x+32=0 | | 3-81=0 | | 4y^2+4y-3=0 | | 2n^2+4n-2=0 | | 4x^2+4=36 | | 81x-21=5+9x |